An antibacterial and blood-promoting pneumothorax sealing patch and a preparation method thereof
By using bisaldehyde carboxymethyl chitosan and tannic acid, combined with an anti-permeable sealing adhesive layer and an outer protective layer of release paper, an antibacterial and pro-coagulant pneumothorax seal patch was solved. There are technology to interfere with the problems of difficulty in stopping bleeding, bacterial infection and slow healing, achieving stronger hemostasis and antibacterial effects, ensuring the safety of the injured.
Patent Information
- Application Number
- CN202211434594.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-16
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-11-16
AI Technical Summary
Existing pneumothoracic sealing is difficult to stop bleeding in a timely manner in a medical environment with poor battlefields, prone to bacterial infections, and the wound healing speed is slow.
Using a hydrogel dressing layer prepared from bisaldehyde carboxymethyl chitosan and tannic acid, combined with an anti-permeable sealing bonding layer and an outer protective layer of release paper, an antibacterial and pro-coagulant pneumothoracic sealing patch is formed, through cross-linking Form a three-dimensional grid-like structure and antibacterial effect of phenolic hydroxyl groups to achieve hemostasis and wound healing.
It provides stronger hemostasis ability, promotes wound healing and antibacterial properties, improves the use effect in adverse environments, and ensures the life safety of the injured.
Smart Images

Figure BDA0003946628610000071
Abstract
Description
Technical Field
[0001] The invention relates to the field of medical supplies, and in particular to an antibacterial and pro-coagulant pneumothorax sealing patch and a preparation method thereof. Background Art
[0002] Traumatic pneumothorax is mostly caused by the lung being punctured by the broken ends of the ribs, or by violent contusions of the bronchus or lung tissue, or by a sharp increase in airway pressure causing rupture of the bronchus or lung. Pneumothorax can also be caused by sharp injuries or firearm injuries that penetrate the chest wall and injure the lungs, bronchi, trachea or esophagus, and are mostly hemothorax or pyopneumothorax. In modern warfare, injuries to the human body caused by fragments, shrapnel, etc. often occur in the chest and abdomen, causing penetrating injuries or deeper blind tube injuries to the chest and abdomen. These injuries are prone to cause open pneumothorax and are accompanied by traumatic hemothorax, which seriously threatens the lives of the wounded and is also an important cause of combat casualties.
[0003] In clinical practice, pneumothorax is usually treated by closing the chest drainage port. The existing method is generally: first cover the wound with a vaseline gauze with a certain degree of airtightness, then bandage it with gauze or cotton pads, and finally fix it with medical tape or film patches. However, due to the complex process and the inconvenience of carrying the required materials and devices, and the many operation processes, it is difficult to apply it in modern warfare. Therefore, a portable pneumothorax sealing patch is available on the market.
[0004] Pneumothorax sealing patches are easy to carry and use. Pneumothorax can be prevented by sealing the wound with pneumothorax sealing patches. Pneumothorax sealing patches usually use polyurethane composite films and one side is sealed with medical hot melt adhesive. This type of sealing patch can quickly seal the wound and prevent the formation of pneumothorax. However, on the battlefield, the medical environment is poor and there are a large number of bacteria. In addition, wounds are often accompanied by a large amount of bleeding. If the bleeding is not stopped in time, blood will flow into the chest cavity to form a hemothorax. In addition, the wound heals slowly and is prone to rupture during the transfer of the wounded, which can worsen the injury.
[0005] In summary, there is an urgent need for a pneumothorax sealing patch that can stop bleeding in time, resist bacterial infection, and promote wound healing in a poor medical environment on the battlefield. Summary of the invention
[0006] Purpose of the invention: In view of the defects of the prior art, the purpose of the present invention is to provide an antibacterial and pro-coagulant pneumothorax sealing patch and a preparation method thereof, so as to solve the problems in the prior art that it is difficult to stop bleeding from wounds, bacterial infection is prone to occur, and the wound healing speed is slow.
[0007] Technical solution:
[0008] An antibacterial and procoagulant pneumothorax sealing patch comprises, from top to bottom, an outer protective layer, a dressing layer and a sealing adhesive layer;
[0009] The dressing layer is composed of a complex prepared from dialdehyde carboxymethyl chitosan and tannic acid, and then the dialdehyde carboxymethyl chitosan in the complex is grafted with acrylic acid, and then a hydrogel is formed by cross-linking.
[0010] The present invention uses carboxymethyl chitosan, and utilizes its hydroxyl groups to provide grafting sites so as to be further modified. At the same time, as an amphoteric polyelectrolyte, it has good water solubility, film-forming property and water absorption and water-containing properties, and can be used as a raw material for hydrogel.
[0011] Tannic acid has strong antibacterial ability because of the large amount of phenolic hydroxyl groups in its structure, which can hinder the bacteria's uptake of iron, polysaccharides, amino acids, etc., destroy bacterial cell walls and cell membranes, and inhibit the formation of biofilms. At the same time, tannic acid can act as an astringent, stimulate the secretion of basic fibroblast growth factor, and accelerate wound healing in vivo and in vitro.
[0012] The hydrogel formed by cross-linking has good biosafety and tissue compatibility and is an excellent hemostatic material. Acrylic acid is grafted on the hydroxyl site of dialdehyde carboxymethyl chitosan, and then a three-dimensional grid structure is formed by a cross-linking agent to form a hydrogel dressing layer.
[0013] Furthermore, the outer protective layer is a release paper outer protective layer.
[0014] Furthermore, the sealing adhesive layer is selected from one of PE, EVA, PEVA, polyurethane or natural rubber with anti-permeability.
[0015] Furthermore, the preparation method of the dialdehyde carboxymethyl chitosan comprises the following steps:
[0016] (1) After adding deionized water into the reactor, add carboxymethyl chitosan and stir to dissolve, then add an oxidant and adjust the pH of the system to 3.5-4;
[0017] (2) heating the reactor of step (1) to 40-45° C. and stirring for 4-5 hours in a dark environment;
[0018] (3) adding ethylene glycol solution to the reactor of step (2), stirring at room temperature for 0.5-1 hour, centrifuging and washing the product, and freeze-drying under vacuum for 20-24 hours to obtain the dialdehyde carboxymethyl chitosan.
[0019] On the basis of carboxymethyl chitosan, new active groups, aldehyde groups, are generated through selective oxidation, which can act as part of the cross-linking function and reduce the use of toxic cross-linking agents.
[0020] Furthermore, in step (1), the oxidant is sodium periodate.
[0021] Furthermore, the tannic acid is medicinal tannic acid, which meets the national industry standards LY-T 1300, LY-T1640, and LY-T1641, has high purity and low heavy metal content, and can be used in the medical field.
[0022] The method for preparing the antibacterial and procoagulant pneumothorax sealing patch comprises the following steps:
[0023] (1) After adding deionized water into the reactor, dialdehyde carboxymethyl chitosan is added and stirred to dissolve, and then a biological buffer is added to adjust the pH of the system to 8-8.5, and then tannic acid is added and mixed evenly, and the mixture is reacted at room temperature for 6-8 hours;
[0024] (2) continuously introducing protective gas into the reactor of step (1), then adding initiator and acrylic acid and stirring evenly, reacting at room temperature for 4-5 hours, and then standing for 10-12 hours;
[0025] (3) adding a crosslinking agent to the reactor of step (2), stirring evenly and sealing the mixture, and then standing at room temperature for 10-12 hours to obtain the dressing layer;
[0026] (4) Placing the dressing layer of step (3) on the upper part of the sealing adhesive layer, and covering the sealing adhesive layer and the dressing layer with an outer protective layer, thereby obtaining the antibacterial and procoagulant pneumothorax sealing patch.
[0027] Step (1) preparing a complex of dialdehyde carboxymethyl chitosan and tannic acid.
[0028] Step (2) grafting acrylic acid onto the hydroxyl sites of dialdehyde carboxymethyl chitosan.
[0029] Step (3) cross-linking to form a hydrogel.
[0030] Furthermore, the mass ratio of the dialdehyde carboxymethyl chitosan, tannic acid and acrylic acid is (1-1.5):(3-5):(10-15).
[0031] Furthermore, in step (1), the biological buffer is selected from one of tris(hydroxymethyl)aminomethane, N,N-dihydroxyethylglycine or 4-hydroxyethylpiperazineethanesulfonic acid.
[0032] The buffer selected by the present invention is a biological buffer, which has good buffering capacity, little interference with biochemical processes and no toxicity to cells.
[0033] Furthermore, in the step (2), the initiator is selected from azobisisopropylimidazoline hydrochloride or dimethyl azobisisobutyrate.
[0034] The initiator used in the present invention is selected from an initiator without a cyano group. Compared with other initiators, the decomposition product is non-toxic, less harmful to the body, and the decomposition is stable and the conversion rate is high.
[0035] Furthermore, in step (3), the cross-linking agent is selected from 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride or N-hydroxysuccinimide.
[0036] The crosslinking agent used in the present invention is a non-toxic crosslinking agent with good biocompatibility. When used in combination with dialdehyde carboxymethyl chitosan with a certain self-crosslinking ability, it has the characteristics of being non-toxic and having good biocompatibility while ensuring a sufficient crosslinking degree.
[0037] Beneficial effects:
[0038] 1. The pneumothorax sealing patch provided by the present invention uses dialdehyde carboxymethyl chitosan, which is a natural polyaminopolysaccharide linear polymer compound, which has a broad-spectrum antibacterial property, good biocompatibility, and no toxic side effects on the human body. The electrostatic reaction between the cathode of the red blood cell membrane and the anode on the surface of the chitosan can be used to stop bleeding.
[0039] The present invention uses carboxymethyl chitosan, and utilizes its hydroxyl group to provide grafting sites so that it can be further modified. At the same time, as an amphoteric polyelectrolyte, it has good water solubility, film-forming property and water absorption and water-encapsulation property, and can be used as a raw material for hydrogel. New active groups, aldehyde groups, are generated by selective oxidation on the basis of carboxymethyl chitosan, which can act as part of the cross-linking function by itself, thereby reducing the use of toxic cross-linking agents.
[0040] 2. Tannic acid is added to the pneumothorax sealing patch provided by the present invention. Tannic acid has excellent spectrum antibacterial activity and also has the ability to promote wound healing. Tannic acid has a strong antibacterial ability because of the large amount of phenolic hydroxyl groups contained in its structure, which can hinder the bacteria from taking in iron, polysaccharides, amino acids, etc., destroy bacterial cell walls and cell membranes, and inhibit the formation of biofilms; Tannic acid can be used as an astringent to stimulate the secretion of basic fibroblast growth factor and accelerate wound healing in vivo and in vitro.
[0041] 3. The pneumothorax sealing patch provided by the present invention uses a hydrogel structure. The hydrogel is a substance composed of an infinite three-dimensional network and water. It can exchange with body fluids and provide nutrients for the growth of cells and tissues. Therefore, it has good biosafety and tissue compatibility and is an excellent hemostatic material. Acrylic acid is grafted on the hydroxyl site of dialdehyde carboxymethyl chitosan, and then a three-dimensional grid structure is made by a cross-linking agent. The grids are interconnected, so that it has good water absorption. When it contacts blood, it can absorb plasma and concentrate blood, which is conducive to platelet aggregation and improves the hemostatic effect.
[0042] 4. The pneumothorax sealing patch provided by the present invention is non-toxic and has excellent biocompatibility: the buffer selected by the present invention is a biological buffer, which has good buffering capacity, little interference with biochemical processes and no toxicity to cells; the initiator selected by the present invention is selected from an initiator without cyano group, and compared with other initiators, the decomposition product is non-toxic, less harmful to the body, and the decomposition is stable and the conversion rate is high; the cross-linking agent selected by the present invention is a non-toxic cross-linking agent with good biocompatibility. When used in combination with dialdehyde carboxymethyl chitosan with a certain self-cross-linking ability, it also has the characteristics of non-toxicity and good biocompatibility while ensuring sufficient cross-linking degree. DETAILED DESCRIPTION
[0043] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0044] The carboxymethyl chitosan used in this application was purchased from Shandong Fengtai Biotechnology Co., Ltd.; tannic acid was purchased from Zhangjiajie Jiurui Biotechnology Co., Ltd. for medicinal tannic acid; the absorbable hemostatic membrane was purchased from Beijing Daqing Biotechnology Co., Ltd. for Daqing Biopaper; the chest seal was purchased from Shenyang Pengyue Technology Co., Ltd. for Pengyue PY191; and the compact chest seal was purchased from North American Rescue, Inc. for NAR HyFin. The remaining reagents and equipment were conventional reagents and equipment in the technical field.
[0045] Preparation of dialdehyde carboxymethyl chitosan
[0046] (1) After adding deionized water into the reactor, 5 parts of carboxymethyl chitosan were added and stirred to dissolve, and then 5 parts of sodium periodate were added to adjust the pH of the system to 4;
[0047] (2) heating the reactor of step (1) to 45° C. and stirring for 4 hours in a dark environment;
[0048] (3) adding ethylene glycol solution to the reactor of step (2), stirring at room temperature for 1 hour, washing the product by centrifugation with tert-butyl alcohol for 3 times, and freeze-drying under vacuum for 24 hours to obtain the dialdehyde carboxymethyl chitosan.
[0049] Example 1
[0050] (1) After adding 30 parts by weight of deionized water into a reactor, 1 part of dialdehyde carboxymethyl chitosan was added and stirred to dissolve, and then tris(hydroxymethyl)aminomethane solution was added to adjust the pH of the system to 8.5, and then 3 parts of tannic acid were added and mixed evenly, and the mixture was reacted at room temperature for 6 hours;
[0051] (2) nitrogen was continuously introduced into the reactor of step (1), and then 0.05 parts of azodiisopropylimidazoline hydrochloride and 10 parts of acrylic acid were added and stirred evenly, reacted at room temperature for 4 hours, and then allowed to stand for 12 hours;
[0052] (3) Add 0.05 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to the reactor of step (2), stir evenly, seal the mixture, and then let it stand at room temperature for 12 hours to obtain a dressing layer.
[0053] (4) Placing the dressing layer of step (3) on the upper part of the sealing adhesive layer, and covering the sealing adhesive layer and the dressing layer with an outer protective layer, thereby obtaining the antibacterial and procoagulant pneumothorax sealing patch.
[0054] Example 2
[0055] The same as in Example 1, except that the amount of tannic acid was changed to 5 parts.
[0056] Example 3
[0057] The same as Example 1, except that the amount of acrylic acid was changed to 15 parts.
[0058] Example 4
[0059] The method is basically the same as Example 1, except that the amount of dialdehyde carboxymethyl chitosan is changed to 1.5 parts.
[0060] Comparative Example 1
[0061] The method is basically the same as Example 1, except that tannic acid is replaced by an equal amount of sodium hyaluronate.
[0062] Comparative Example 2
[0063] The process is basically the same as in Example 1, except that an equal amount of methylenesuccinic acid is used instead of acrylic acid.
[0064] Comparative Example 3
[0065] The method is basically the same as Example 1, except that the dialdehyde carboxymethyl chitosan is replaced by an equal amount of carboxymethyl chitosan.
[0066] Comparative Example 4
[0067] Absorbable hemostatic membrane.
[0068] Comparative Example 5
[0069] Chest seal patch.
[0070] Comparative Example 6
[0071] Compact chest closure.
[0072] Performance Testing
[0073] 1. Water absorption strength test: 0.5g of the products of Examples 1-4 and 0.5g of the products of Comparative Examples 1-4 were placed in a 1000ml beaker, 500ml of distilled water was added, and the mixture was allowed to stand at room temperature for six hours. After the mixture reached saturation, the distilled water was filtered out, the mass was weighed, and the water absorption rate was calculated. The results are shown in the following table.
[0074] Sample (m / g) Water absorption (m / g) Water absorption (g / g) Example 1 0.5 60 120 Example 2 0.5 62 124 Example 3 0.5 59 118 Example 4 0.5 60 120 Comparative Example 1 0.5 46 92 Comparative Example 2 0.5 52 104 Comparative Example 3 0.5 53 106 Comparative Example 4 0.5 50 100
[0075] According to the comparison between Examples 1-4 and Comparative Example 4, it can be seen that the pneumothorax sealing patch provided by the present invention has stronger water absorption capacity, and thus has stronger hemostatic ability. According to the comparison between Examples 1-4 and Comparative Examples 1-3, it can be seen that tannic acid has excellent water absorption capacity, and the use of acrylic acid graft modification and dialdehyde carboxymethyl chitosan can make the prepared hydrogel have better water absorption capacity.
[0076] 2. Hemostasis ability test: The big-eared white rabbits were randomly divided into 11 groups. After being anesthetized, the big-eared white rabbits were fixed on the operating table. The femoral vein was exposed and transversely cut. After it was allowed to bleed freely for 10 seconds, the products of Examples 1-4 and Comparative Examples 1-6 were used to stop bleeding from the wounds, and gauze squeeze hemostasis was used as a blank control to observe the hemostasis time.
[0077] Procoagulant ability test: The wounds of the rabbits were photographed every 2 days after the injury, and the wound area of the rabbits was calculated using Image-Pro Plus Version 6.0 image analysis software until the wounds healed.
[0078] Healing rate = (original wound area - unhealed wound area) / original wound area x 100%. The results are shown in the following table.
[0079]
[0080] According to the comparison between Examples 1-4 and Comparative Examples 4-6 and the blank control, in terms of hemostatic ability, the pneumothorax sealing patch provided by the present invention has hemostatic ability, and has stronger hemostatic ability than conventional hemostatic membranes, and can complete hemostasis in a shorter time; in terms of procoagulant ability, the pneumothorax sealing patch provided by the present invention has basically healed the wound on the 10th day, and has stronger self-healing ability than large-eared white rabbits, achieving the effect of promoting healing, and is also stronger than the procoagulant ability of other pneumothorax sealing patches and hemostatic products. According to the comparison between Examples 1-4 and Comparative Examples 1-3, it can be seen that tannic acid has better hemostatic and procoagulant abilities than sodium hyaluronate, and the use of acrylic acid grafting modification and the use of dialdehyde carboxymethyl chitosan can make the prepared hydrogel have better hemostatic and procoagulant abilities.
[0081] 3. Antibacterial ability test: According to the ASTM 21-96 method for determining the antifungal property of synthetic polymer materials, the mildew resistance performance test of the product was carried out by the culture dish method. The samples prepared in Examples 1-4 and Comparative Examples 1-4 were made into 50mm×50mm specifications and placed flat on the surface of the solidified inorganic salt culture medium. Then a mixed suspension of fungal spores was prepared: 5 kinds of molds (Aspergillus niger, Penicillium funiculum, Chaetomium globosum, Gliocladium virens, and Aureobasidium raphis). The prepared spore suspension used spores (1000000±200000) / mL, which can be calculated using a counter. The fungal spore suspension was evenly and finely sprayed on the entire surface of the sample, and the sprayer pressure should reach 110 kPa. After drying slightly, cover the culture dish with a lid. The lid was marked with the sample name, number and date, and placed in an incubator, maintained at a temperature of 28°C to 30°C and a relative humidity of not less than 85%. The standard incubation time for the test was 28 days, and the mildew resistance grade was evaluated after 28 days. The results are shown in the following table.
[0082] Mildew resistance level Example 1 0 Example 2 0 Example 3 0 Example 4 0 Comparative Example 1 2 Comparative Example 2 1 Comparative Example 3 1 Comparative Example 4 3 Comparative Example 5 3 Comparative Example 6 4
[0083] The evaluation standards for mildew resistance levels are shown in the following table.
[0084] Mildew resistance level Mildew resistance level 0 No mold 1 Trace growth (less than 10%) 2 Slight growth (10-30%) 3 Moderate growth (30-60%) 4 Severe growth (60% - full coverage)
[0085] According to the comparison between Examples 1-4 and Comparative Examples 4-6, the pneumothorax sealing patch provided by the present invention has a strong antibacterial ability, while the pneumothorax sealing patch and hemostatic products currently on the market have a very poor antibacterial ability. According to the comparison between Examples 1-4 and Comparative Examples 1-3, tannic acid has a strong antibacterial ability, and the use of acrylic acid grafting modification and the use of dialdehyde carboxymethyl chitosan can make the prepared hydrogel have better antibacterial ability.
[0086] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. An antibacterial and procoagulant pneumothorax sealing patch, characterized in that: It includes an outer protective layer, a dressing layer and a sealing adhesive layer from top to bottom; The dressing layer is composed of a complex prepared from dialdehyde carboxymethyl chitosan and tannic acid, and then dialdehyde carboxymethyl chitosan in the complex is grafted with acrylic acid, and then a hydrogel is formed by cross-linking; The preparation method of the dialdehyde carboxymethyl chitosan comprises the following steps: (1) After adding deionized water into the reactor, add carboxymethyl chitosan and stir to dissolve, then add sodium periodate and adjust the pH of the system to 3.5-4; (2) heating the reactor in step (1) to 40-45°C and stirring for 4-5 hours in a dark environment; (3) adding ethylene glycol solution to the reactor of step (2), stirring at room temperature for 0.5-1 hour, centrifuging and washing the product, and freeze-drying under vacuum for 20-24 hours to obtain the dialdehyde carboxymethyl chitosan; The antibacterial and procoagulant pneumothorax sealing patch is prepared by the following steps: (1) After adding deionized water into the reactor, add dialdehyde carboxymethyl chitosan and stir to dissolve, then add biological buffer to adjust the pH of the system to 8-8.5, add tannic acid and mix well, and react at room temperature for 6-8 hours; (2) continuously introducing protective gas into the reactor of step (1), then adding initiator and acrylic acid and stirring evenly, reacting at room temperature for 4-5 hours, and then standing for 10-12 hours; (3) adding a crosslinking agent to the reactor of step (2), stirring evenly and sealing the mixture, and then standing at room temperature for 10-12 hours to obtain the dressing layer; (4) placing the dressing layer of step (3) on the upper part of the sealing adhesive layer, and covering the sealing adhesive layer and the dressing layer with an outer protective layer, thereby obtaining the antibacterial and procoagulant pneumothorax sealing patch; The mass ratio of the dialdehyde carboxymethyl chitosan, tannic acid and acrylic acid is (1-1.5): (3-5): (10-15); The biological buffer is selected from one of tris(hydroxymethyl)aminomethane, N,N-dihydroxyethylglycine or 4-hydroxyethylpiperazineethanesulfonic acid; The initiator is selected from one of azobisisopropylimidazoline hydrochloride and dimethyl azobisisobutyrate; The cross-linking agent is selected from one of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide.
2. The antibacterial and procoagulant pneumothorax sealing patch according to claim 1, characterized in that: The outer protective layer is a release paper outer protective layer.
3. The antibacterial and procoagulant pneumothorax sealing patch according to claim 1, characterized in that: The sealing adhesive layer is selected from one of PE, EVA, PEVA, polyurethane or natural rubber with anti-permeability.
